Enhancing Practice Through Classroom Research : a Teacher's Guide to Professional Development - McDonagh, Caitriona (Routledge, 2020)
Offering updated references, questions for reflection, the latest case studies, and current advice relating to data protection and storage, this second edition of Enhancing Practice through Classroom Research provides an accessible introduction to understanding and improving teaching and learning through a process of reflection, research, and action. Divided into five parts, this self-study action research approach emphasises the positive aspects of enhancing practice and reflects how this can lead to higher levels of teacher autonomy and agency. With the addition of a chapter dedicated to the links between action research and well-being, this book provides a step-by-step guide to beginning your own research and covers topics such as: Identifying an area of professional concern or interest Exploration of educational values Developing a better understanding of practice Thinking critically about educational practices Finding a research methodology Drawing on the authors' new experiences of working with second level, third level, and postgraduate educators, as well as their work designing postgraduate programmes in the field of critical reflection and self-study action research, this friendly guide provides a straightforward approach to classroom research. It is the perfect resource for all student and practising teachers looking for support in classroom research, as well as those wanting to pursue effective professional development or further studies in an area of interest.